De los recursos didácticos para el aula a los contenidos para espacios virtuales educativos con componentes activos y herramientas de autor - García Peñalvo, Francisco José (2011)
At least apparently, given today’s infrastructures, both IT and Communications Technologies are becoming real players in the field of educative processes at large, and this is particularly true in appearance and infrastructure. Use of audiovisual means is commonplace as a complement for standard lectures, and so is the publication of various materials in different teaching-related web sites. However, a closer look at the actual situation will perhaps take us to a less pleasant reality, in which the group of educators who produce didactic contents by no means includes all of the human potential that a University could offer. As a consequence, the number of didactic products is affected adversely, and the quality, organization and accessibility of the said products could and should be better. In this paper, which is based on the experience acquired in the Laboratorio de Diseños Educativos Multimedia y Teleeducación del Instituto de Ciencias de la Educación of University of Salamanca, we advocate the need to go beyond the mere creation of isolated teaching elements, thus advancing towards the establishment of authentic virtual teaching spaces. These should be based on active educative components and authoring tools, in such a way that the population of these spaces with quality contents could be a fact. About authoring tools, we claim that author-tool interface must be intended to facilitate and deepen their use for the wide group of content creators who are not versed in computers.